2017
DOI: 10.1177/0194599817696294
|View full text |Cite
|
Sign up to set email alerts
|

Association between Nasal Obstruction and Risk of Depression in Chronic Rhinosinusitis

Abstract: Objective Chronic rhinosinusitis (CRS) is associated with an increased risk for depression. Since nasal obstruction is a symptom of CRS that is treatable, we sought to characterize its impact on the risk for depression in CRS. Study Design Prospective cross-sectional cohort of 94 patients with CRS. Setting Academic tertiary care rhinology clinic. Subjects and Methods Patients with CRS without vasculitis, cystic fibrosis, sarcoidosis, immunodeficiency, or sinonasal malignancy. Risk for depression was assessed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…13 Reported rates of depression in patients with CRS have been between 9% and 40%. 8-10 The current study found that 18.1% of 216 patients had a PHQ-9 score ≥10 (the threshold score, which is suggestive of underlying depression). In a large retrospective cohort study of approximately 1 million patients in Korea, depression and anxiety were more prevalent among patients with CRS, and the risk of developing depression and anxiety was greater in patients with CRS without nasal polyps than in those with CRS with nasal polyps.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…13 Reported rates of depression in patients with CRS have been between 9% and 40%. 8-10 The current study found that 18.1% of 216 patients had a PHQ-9 score ≥10 (the threshold score, which is suggestive of underlying depression). In a large retrospective cohort study of approximately 1 million patients in Korea, depression and anxiety were more prevalent among patients with CRS, and the risk of developing depression and anxiety was greater in patients with CRS without nasal polyps than in those with CRS with nasal polyps.…”
Section: Discussionmentioning
confidence: 55%
“…11 Patients with CRS report lower quality-of-life scores and high rates of poor sleep (60%-75%) as compared with the general population (6%-18%). 10,12 This has an effect on quality of life and productivity. A study of a multiemployer database in the United States showed that sinusitis and depression were among the top 10 most costly health conditions.…”
mentioning
confidence: 99%
“…20 Various validated screening tools (ie, Patient Health Questionnaire-2, Patient Health Questionnaire-9, Hospital Anxiety and Depression Scale, Becks Depression Inventory) are being used to help identify patients with rhinologic complaints who also have symptoms of depression and/or anxiety. [21][22][23][24] Lee et al performed a prospective cohort study of 20 patients with ENS diagnosed by history and physical, undergoing endonasal submucosal implantation with high-density polyethylene or autologous bone grafts. The authors noted an improvement in the preoperative Beck's Depression Inventory II and Beck Anxiety Inventory scores from "moderate" to "normal" after surgical intervention.…”
Section: Mental Health Comorbiditiesmentioning
confidence: 99%
“…The major complaints of patients with CRS, indeed tend to be sinus-specific, including nasal congestion and discharge, facial pain/pressure and/or olfactory disturbances. In addition, some of the less common symptoms, such as fatigue and headache, which are not relevant to sinusitis pathology but rather to a host of other chronic conditions, have also been shown in several studies to have an effect on disease severity ( 3-5 ) In previous studies, psychiatric distress, including workplace disturbances, anxiety and depression, have been reported to be associated with increased symptom burden in CRS patients ( 6 , 7 ) Accordingly, several validated patient-reported measures of outcomes have been utilized since the 1990s to evaluate health-related quality of life. Among them, the Sino-Nasal Outcome Tests (SNOTs), including versions such as the SNOT-16, SNOT-2, and Sino-Nasal Assessment Questionnaire 11 (SNAQ-11), which is a modification of the 31-question Rhinosinusitis Outcome Measure (RSOM-31), has mostly been applied in the past decade ( 8-10 ).…”
Section: Introductionmentioning
confidence: 99%